PENGARUH KOMPETENSI DAN MOTIVASI PEGAWAI TERHADAP KINERJA PEGAWAI SEKRETARIAT DPRD KOTA SEMARANG - Enggar Rayi Pradiningrum; Hesti Larasati; Slamet Santoso (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
The most important component to move the organization in the achievement of the purpose is human resources, so does the Secretariat of the Semarang City local parliament in providing services to members of parliament. In the run tupoksinya, there are complaints on the performance of the Parliament Secretariat of Semarang. Besides, there are mismatches with the occupied areas of competencies owned by employees viewed from educational backgrounds. Employee Income Supplement is still difficult to raise employee motivation because of lack of clarity in the provision of reference and the difference in nominal TPP received by each employee. The purpose of this research was to analyze the relationship between competence and motivation of the employee's performance. Kendalls tau is used to answer the research objectives. This study uses quantitative and respondent types of Semarang Parliament Secretariat. Data collection methods used were interviews, observations, questionnaires, and documentation. Based on the results of this research is that the performance, competence and motivation of employees included in good category. Correlation test showed that there were positive and significant relationship between competence and motivation on employee performance Semarang Parliament Secretariat. It can be concluded that employees who have competence, but not supported by high motivation make the performance not maximal, so increasing motivation and competence development must be done.